Effects of La and Ce Addition on the Modification of Al-Si Based Alloys - Emad M. Elgallad; Herbert W. Doty; Saleh A. Alkahtani; Fawzy H. Samuel (Advances in Materials Science and Engineering)
This study focuses on the effects of the addition of rare earth metals (mainly lanthanum and cerium) on the eutectic Si characteristics in Al-Si based alloys. Based on the solidification curves and microstructural examination of the corresponding alloys, it was found that addition of La or Ce increases the alloy melting temperature and the Al-Si eutectic temperature, with an Al-Si recalescence of 2-3°C, and the appearance of post-α-Al peaks attributed to precipitation of rare earth intermetallics. Addition of La or Ce to Al-(7–13)% Si causes only partial modification of the eutectic Si particles. Lanthanum has a high affinity to react with Sr, which weakens the modification efficiency of the latter. Cerium, however, has a high affinity for Ti, forming a large amount of sludge. Due to the large difference in the length of the eutectic Si particles in the same sample, the normal use of standard deviation in this case is meaningless.